2015
DOI: 10.1073/pnas.1502351112
|View full text |Cite
|
Sign up to set email alerts
|

Delicate conformational balance of the redox enzyme cytochrome P450cam

Abstract: The energy landscapes of proteins are highly complex and can be influenced by changes in physical and chemical conditions under which the protein is studied. The redox enzyme cytochrome P450cam undergoes a multistep catalytic cycle wherein two electrons are transferred to the heme group and the enzyme visits several conformational states. Using paramagnetic NMR spectroscopy with a lanthanoid tag, we show that the enzyme bound to its redox partner, putidaredoxin, is in a closed state at ambient temperature in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(100 citation statements)
references
References 52 publications
9
91
0
Order By: Relevance
“…For example, Pdx binding shifts P450cam from high to low spin (4), indicating that when Pdx binds, the active site opens up, thus allowing water to enter the active site and coordinate to the heme iron. Also consistent with opening of the active site is that Pdx binding destabilizes the P450cam-oxy complex ∼150-fold (5 (10). That the open form was found in the crystal structures and DEER experiments was dismissed as artifacts of crystallization and the low temperature required for the DEER experiments.…”
mentioning
confidence: 70%
“…For example, Pdx binding shifts P450cam from high to low spin (4), indicating that when Pdx binds, the active site opens up, thus allowing water to enter the active site and coordinate to the heme iron. Also consistent with opening of the active site is that Pdx binding destabilizes the P450cam-oxy complex ∼150-fold (5 (10). That the open form was found in the crystal structures and DEER experiments was dismissed as artifacts of crystallization and the low temperature required for the DEER experiments.…”
mentioning
confidence: 70%
“…cytP450cam remains closed on binding to Pdx (30). Low-temperature EPR studies suggested that Pdx binding leads to a mixture of open and closed states for the oxidized cytP450cam but not for the reduced, CO-bound state (31,32).…”
Section: Significancementioning
confidence: 98%
“…It is important to bear in mind here ac onformational change to the enzymatic three-dimensional structure is common after substrate binding. [30] Many docking protocols have been developed in order to try and assess the likelihood of varioussubstrate-binding orientations and positions. [29] As can be seen, the major differences in protein folding are observed mostly in the Fa nd Gh elices that form the flexible loop domain [29b] (inside the green rectangle) and it can be hypothesized that substrate binding will closealid of the protein and functions as at rigger to initiate the catalytic cycle.…”
Section: Substrate Dockingmentioning
confidence: 99%